1987
DOI: 10.1007/bf01541713
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three methods of scoring penile circumference changes

Abstract: There are presently three widely used methods of scoring penile circumference data. The present experiment attempted to determine the ability of each method to explain the variance within a data set. A total of 19 subjects were presented with 20 photographic slides assigned to five categories: neutral, female adult, female adolescent, male adult, and male adolescent. Erectile responses to each slide were recorded and the data analyzed in terms of the raw scores, percentage of full erection, and a z-score trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 11 publications
1
35
0
Order By: Relevance
“…There are numerous sources of such variability, for example, the participant's age, his state of health, the size of his penis, and the amount of time since his last ejaculation from masturbation or interpersonal sexual activity. Empirical research has shown the Z-score transformation to be optimal (Earls, Quinsey, & Castonguay, 1987;Harris, Rice, Quinsey, Chaplin, & Earls, 1992;Langevin, 1985). (b) The (highly correlated) area and extremum Z-scores were averaged to obtain a composite that reflected both the speed and amplitude of response and lessened the impact of anomalous responses, that is, large change from initial value but small area or vice versa (Freund, Scher, & Hucker, 1983).…”
Section: Phallometric Response Processingmentioning
confidence: 99%
“…There are numerous sources of such variability, for example, the participant's age, his state of health, the size of his penis, and the amount of time since his last ejaculation from masturbation or interpersonal sexual activity. Empirical research has shown the Z-score transformation to be optimal (Earls, Quinsey, & Castonguay, 1987;Harris, Rice, Quinsey, Chaplin, & Earls, 1992;Langevin, 1985). (b) The (highly correlated) area and extremum Z-scores were averaged to obtain a composite that reflected both the speed and amplitude of response and lessened the impact of anomalous responses, that is, large change from initial value but small area or vice versa (Freund, Scher, & Hucker, 1983).…”
Section: Phallometric Response Processingmentioning
confidence: 99%
“…The strain gauge was calibrated for a range of 40mm, with the flaccid measurement as the minimum circumference. The use of the mercury-in-rubber strain gauge to measure changes in penile tumescence has been shown to be a reliable and valid measure (Laws, 1977;Farkas, Evans, Sine, Eifert, Wittlieb, & VogelmannSine, 1979;Earls, Quinsey, & Castonguay, 1987) 3.…”
mentioning
confidence: 99%
“…As well, useful information on the original magnitude of arousal is lost (Adler, 1994). In a study by Earls, Quinsey, and Castonguay (1987), z scores were found to describe the significantly highest proportion of variance (52.7%) in comparison to %FE (32.5%) and raw scores (30.1%). This was supported by Harris, Rice, Quinsey, Chaplin, and Earls (1992), who found z scores to be slightly superior to percentage of full erection.…”
Section: Statistical Issuesmentioning
confidence: 92%